2016
DOI: 10.1155/2016/9687052
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Stenting Reduces Post-ERCP Pancreatitis and Biliary Sepsis in High-Risk Patients: A Randomized, Controlled Study

Abstract: Background. Endoscopic retrograde cholangiopancreatography (ERCP) is an established treatment modality for bile duct disorders, but patients have a risk of post-ERCP pancreatitis (PEP) and biliary sepsis. Aim. To evaluate the effectiveness and safety of pancreatic stent for prophylaxis of PEP and biliary sepsis in high-risk patients with complicating common bile duct (CBD) disorders. Methods. Two hundred and six patients with complicating confirmed or suspected CBD disorders were randomly assigned to receive E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…These findings suggest that the flange on the PD side influences the spontaneous passage of the PS. An important technical factor, which may influence the type of temporary prophylactic PS chosen, is the technical ease of placement because prolonged and unsuccessful attempts at placement may potentially increase the risk of developing PEP 21 . In our series, the 5‐Fr PS was successfully placed for the prophylaxis of PEP in all cases.…”
Section: Discussionmentioning
confidence: 81%
“…These findings suggest that the flange on the PD side influences the spontaneous passage of the PS. An important technical factor, which may influence the type of temporary prophylactic PS chosen, is the technical ease of placement because prolonged and unsuccessful attempts at placement may potentially increase the risk of developing PEP 21 . In our series, the 5‐Fr PS was successfully placed for the prophylaxis of PEP in all cases.…”
Section: Discussionmentioning
confidence: 81%
“…Pre-ERCP administration of rectal indometacin reduced the overall occurrence of PEP without increasing risk of bleeding[34]. Some studies reported that the combination of a temporary prophylactic pancreatic plastic stent placement and rectal non-steroidal anti-inflammatory drugs is recommended for preventing PEP in high-risk cases[34-36]. Somatostatin can reduce the incidence of PEP but has not been routinely administrated in most of centers nor recommended by guidelines as a prophylactic measure for PEP[36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the combination of a temporary prophylactic pancreatic plastic stent placement and rectal non-steroidal anti-inflammatory drugs is recommended for preventing PEP in high-risk cases[34-36]. Somatostatin can reduce the incidence of PEP but has not been routinely administrated in most of centers nor recommended by guidelines as a prophylactic measure for PEP[36,37]. Patients at high risk of PEP should be also monitored for at least 24 h to avoid occurrence of PEP after early discharge[1,7].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the overall frequency of PEP was 11.3%, and the frequency of PEP was significantly lower in the pancreatic stent placement group than that in the non-placement group (7.9 vs. 15.2%, p = 0.0021), although there were no significant differences in an intention-to-treat analysis (p = 0.076). On the other hand, Yin et al [23] performed a randomized study of a total of 206 patients. In this study, PEP occurred in 12.6% (26/206), and the stent placement group had a significantly lower frequency of PEP than that in the non-stent placement group (7.7 vs. 17.7%, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%